Algorithms and the End of Politics How Technology Shapes 21st-Century American Life - Timcke, Scott (Bristol University Press, 2021)
EPDF available Open Access under CC-BY-NC-ND licence. This timely study considers the growing impacts of digital technologies on populism in the US and beyond. Analysing the rise of digital devices, social networks and the technology giants behind them, Timcke provides new perspectives on data politics and digital and economic sociology demonstrating the power of algorithms on political legitimism and everyday life.